Morphology of Female Genitalia of Xylotrechus basifuliginosus Heller, 1926 (Coleoptera: Cerambycidae: Clytini) - Ramola, Gaurav Chand; Singh, Arun Pratap (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Female genitalia have been largely neglected in studies of genital evolution, perhaps due to the long-standing belief that they are relatively invariable and therefore taxonomically and evolutionarily uninformative in comparison with male genitalia. In the present study, the female genital structure of lesser known beetle, Xylotrechus basifuliginosus was examined for the first time for morphological descriptions using advanced microscopy techniques and dissection methods and compared with its female congener, Xylotrechus smei (Castelnau & Gory). In X. basifuliginosus, the tergite and sternite are generally equal in length. Fully extended genitalia is 3.78mm long from the proximal edge of 9th segment and 0.37mm at its widest.8th abdominal segment is 0.65mm long, 0.36 mm wide whereas eighth abdominal segment is 1.2 times longer than wide, apico-lateral margin, covered with intermix of few short and long setae in X. smei. The genital pocket is 1.36 mm long-scissor like, cylindrical in shape, strongly sclerotized. Spermatheca duct is reduced, “J” shaped just like the genera of Chlorophorus and Plagionotus spp. Spiculum gastrale is 1.34 mm long, thin, slightly thickened at tip and almost three times the length of sternite 8 and ovipositor is 2.19 mm long, 0.85 mm wide, elongated and gradually narrows down to posterior end in X. basifuliginosus whereas in X. smei, spiculum gastrale is 3.43 mm long; ovipositor is with distinct paraproct, gonocoxite and gonostylus and surface of gonostylus is with few setae.